GE_GERICHTE C/2370/2008 vom 5. Dezember 2008 - GE Cour de justice (2008)
; ENFANT ; DOMICILE ÉLU ; DOMICILE À L'ÉTRANGER ; COMPÉTENCE RATIONE LOCI | LPC.73.3. LPC.73.2. LPC.76.2. LPC.75.2. LDIP.64.1. LDIP.85.1